Sustainable urban development. Organizing information content for the transition to Positive Energy Districts - Tiziana Ferrante; Federica Romagnoli; Teresa Villani (Agathón)
In line with the strategies to promote Positive Energy Districts for a transition to climate-neutral European cities, the contribution reports the outcomes of a research aimed at detecting the enabling factors to incentivize such a transition in the national territory, identifying the role played by the main public and private stakeholders in the different phases. Starting from the study of implementation processes, technological solutions and stakeholder involvement methods that have contributed to the success of virtuous sustainable urban development projects implemented in Italy, the research proposes a systemic approach for the organization of relevant information content capable of supporting Municipalities in identifying potentially replicable good practices, incentivizing them to initiate new urban development processes in Positive Energy Districts.